2017
DOI: 10.1186/s12870-017-1091-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analysis reveals differentially expressed genes associated with sex expression in garden asparagus (Asparagus officinalis)

Abstract: BackgroundGarden asparagus (Asparagus officinalis) is a highly valuable vegetable crop of commercial and nutritional interest. It is also commonly used to investigate the mechanisms of sex determination and differentiation in plants. However, the sex expression mechanisms in asparagus remain poorly understood.ResultsDe novo transcriptome sequencing via Illumina paired-end sequencing revealed more than 26 billion bases of high-quality sequence data from male and female asparagus flower buds. A total of 72,626 u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 86 publications
1
30
0
Order By: Relevance
“…3 ). The differential expression of ABCE floral organ-identity genes has been implicated in the regulation of male and female flower development [ 60 , 61 ]. Thus it suggested that cytokinin could directly target the floral organ-identity genes in the regulation of sex determination.…”
Section: Discussionmentioning
confidence: 99%
“…3 ). The differential expression of ABCE floral organ-identity genes has been implicated in the regulation of male and female flower development [ 60 , 61 ]. Thus it suggested that cytokinin could directly target the floral organ-identity genes in the regulation of sex determination.…”
Section: Discussionmentioning
confidence: 99%
“…Plant sex differentiation is closely related to plant hormones, such as ethylene, which is considered as a potent sex hormone in cucumbers that can induce formation of female flowers (Trebitsh et al 1987 ; Rudich et al 1972 ; Li et al 2017 ). Another example is the gibberellins, which can promote the formation of male flowers via ethylene-dependent and ethylene-independent pathways in cucumber (Hao et al 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…One MADS box gene in the shrub willow ( Salix suchowensis ) was recorded to express significantly higher in the female flower buds than in the males [ 58 ]. Several MADS box TF genes in the garden asparagus ( A. officinalis ) also expressed differentially in the two sex types of flower buds [ 59 ]. In this study, 100 putative MASD box unigenes were identified from the E. ulmoides transcriptome data ( Table S3 ), this number is similar as the MADS box genes (112) found in tomato ( Solanum lycopersicum ) [ 60 ].…”
Section: Discussionmentioning
confidence: 99%